Tinjauan Du Point System Untuk Mengukur Kinerja Keuangan Pada Perusahaan Farmasi yang Terdaftar di Bursa Efek Indonesia - Natsir, Ulfa (Amsir Management Journal, 2023)
This study aims to determine the extent of financial performance in pharmaceutical companies listed on the Indonesia Stock Exchange using the Du Pont System method, for three years (2018-2020), The data analysis technique used in this study is quantitative by calculating Net Profit Margin (NPM), Debt Ratio (DR), Total Asset Turnover (TATO). Return On Investment (ROI), Return On Equity (ROE). The results of this study show that at PT. Kimia Farma Tbk, PT. Darya Varia Laboratoria Tbk, and PT. Kalbe Farma Tbk's financial performance tends to fluctuate up and down or fluctuate so it can be concluded that the financial performance of PT. Kimia Farma Tbk, PT. Darya Varia Laboratoria Tbk, and PT. Kalbe Farma Tbk is in the category of not according to industry standards, because the average ROI, ROE, and TATO level are below the assessment standard.